Protein S-nitrosation differentially modulates tomato responses to infection by hemi-biotrophic oomycetes of Phytophthora spp - Jedelská, Tereza; Sedlářová, Michaela; Lochman, Jan; Činčalová, Lucie; Luhová, Lenka; Petřivalský, Marek (Horticulture research, 2021)
Regulation of protein function by reversible S-nitrosation, a post-translational modification based on the attachment of nitroso group to cysteine thiols, has emerged among key mechanisms of NO signalling in plant development and stress responses. S-nitrosoglutathione is regarded as the most abundant low-molecular-weight S-nitrosothiol in plants, where its intracellular concentrations are modulated by S-nitrosoglutathione reductase. We analysed modulations of S-nitrosothiols and protein S-nitrosation mediated by S-nitrosoglutathione reductase in cultivated Solanum lycopersicum (susceptible) and wild Solanum habrochaites (resistant genotype) up to 96 h post inoculation (hpi) by two hemibiotrophic oomycetes, Phytophthora infestans and Phytophthora parasitica. S-nitrosoglutathione reductase activity and protein level were decreased by P. infestans and P. parasitica infection in both genotypes, whereas protein S-nitrosothiols were increased by P. infestans infection, particularly at 72 hpi related to pathogen biotrophy-necrotrophy transition. Increased levels of S-nitrosothiols localised in both proximal and distal parts to the infection site, which suggests together with their localisation to vascular bundles a signalling role in systemic responses. S-nitrosation targets in plants infected with P. infestans identified by a proteomic analysis include namely antioxidant and defence proteins, together with important proteins of metabolic, regulatory and structural functions. Ascorbate peroxidase S-nitrosation was observed in both genotypes in parallel to increased enzyme activity and protein level during P. infestans pathogenesis, namely in the susceptible genotype. These results show important regulatory functions of protein S-nitrosation in concerting molecular mechanisms of plant resistance to hemibiotrophic pathogens.